20 questions about youth and media/edited by Sharon R. Mazzerella - "Mazzerella, Sharon R. (ed.)" (New York, 2007)
20 Questions is a comprehensive guide to today's most pressing issues in the study of children, tweens, and teens and the media. Sharon R. Mazzarella brings together leading experts to address a range of topics from government regulation and the effects of violent entertainment to the commercialization of youth culture and self-identity. This book is designed with the classroom in mind, with accessible writing and end-of-chapter questions.
Keywords: mass media & youth-United states